Development of Interactive Learning Media using Scracth to Increase Students' Motivation to Learn - Fajira, Ira; Ahyar, Ahyar; Hakim, Arif Rahman (FKIP - Universitas Riau, 2025)
This research was conducted to overcome the problem of low student learning motivation in Informatics subjects at SMPN 2 Hu'u which is often caused by conventional learning methods and limitations of interactive media. The purpose of this research is to develop Scratch-based interactive learning media that is able to increase student motivation and involvement in the learning process. This development follows the ADDIE model which consists of Analyze, Design, Development, Implementation, and Evaluation stages. Data collection was carried out through observation, interviews, expert validation, and practicality questionnaires involving teachers and students. The results of expert validation showed that the media was in the very feasible category with an overall score above 80 percent, while the practicality test showed a positive response from both teachers and students with an average score above 85 percent. These findings prove that Scratch-based media is not only feasible and practical but also effective in creating a fun and interactive learning atmosphere. In conclusion, the media developed in this study can be considered as an innovative solution to increase students' motivation to learn and improve the quality of Informatics education in schools